La Agricultura y la Élite Agraria Chilena a Través de Los Catastros Agrícolas, C.1830-1855 - Robles-Ortiz, C; Navarrete-Montalvo, J; Llorca-Jana, M; Araya-Valenzuela, R (Pontificia Universidad Catolica de Chile, 2017)
This article assesses the state of the agrarian sector and the composition of the Chilean agrarian elite during the first half of the nineteenth century, a rather unexplored period in Chile s agrarian historiography. We have used several untapped sources such as the Catastro Agrícola and El Agricultor. From the former we have built and processed a half a million records database. From the former we have built and processed a database consisting of half a million records from the first three agricultural censuses of 1832, 1838 and 1852. We have explained why the agricultural sector was so backwards in Chile, while also established a very unequal distribution of both land tenure and agricultural income. Finally, our results show a great persistence within the composition of the agrarian elites between late colonial times and the first decades of republican Chile, as well as a significant correlation between the large landowners with highest agricultural income and the political elite. © Historia (Santiago) 2017.